PENERAPAN METODE DECISION TREE UNTUK PRAKIRAAN CUACA KOTA BEKASI - Kristopher Halim; Dyah Erny Herwindiati; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
To predict the weather requires a lot of weather data variables, many influencing factors such as the large amount of data. Because this makes prediction accuracy and speed less accurate. So with that made a way to make predictive model research using several data mining techniques. The data to be used in this study were obtained from timeanddate.com, timeanddate.com is a site that provides data and information about daily weather conditions. The data used ranges from December 2021 to August 2022. The research aims to obtain weather classification patterns using the data mining classification algorithm, namely the C4.5 algorithm. The results of testing the C4.5 algorithm using the php website and program get an accuracy of 82%.